Revision Anterior Cruciate Ligament Reconstruction after Surgical Management of Multiligament Knee Injury - Worley, John R.; Brimmo, Olubusola; Nuelle, Clayton W.; Zitsch, Bradford P.; Leary, Emily V.; Cook, James L.; Stannard, James P. (The Journal of Knee Surgery, 2020)
The purpose of this study is to determine factors associated with the need for revision anterior cruciate ligament reconstruction (ACLR) after multiligament knee injury (MLKI) and to report outcomes for patients undergoing revision ACLR after MLKI. This involves a retrospective review of 231 MLKIs in 225 patients treated over a 12-year period, with institutional review board approval. Patients with two or more injured knee ligaments requiring surgical reconstruction, including the ACL, were included for analyses. Overall, 231 knees with MLKIs underwent ACLR, with 10% (n = 24) requiring revision ACLR. There were no significant differences in age, sex, tobacco use, diabetes, or body mass index between cohorts requiring or not requiring revision ACLR. However, patients requiring revision ACLR had significantly longer follow-up duration (55.1 vs. 37.4 months, p = 0.004), more ligament reconstructions/repairs (mean 3.0 vs. 1.7, p < 0.001), more nonligament surgeries (mean 2.2 vs. 0.7, p = 0.002), more total surgeries (mean 5.3 vs. 2.4, p < 0.001), and more graft reconstructions (mean 4.7 vs. 2.7, p < 0.001). Patients in both groups had similar return to work (p = 0.12) and activity (p = 0.91) levels at final follow-up. Patients who had revision ACLR took significantly longer to return to work at their highest level (18 vs. 12 months, p = 0.036), but similar time to return to their highest level of activity (p = 0.33). Range of motion (134 vs. 127 degrees, p = 0.14), pain severity (2.2 vs. 1.7, p = 0.24), and Lysholm's scores (86.3 vs. 90.0, p = 0.24) at final follow-up were similar between groups. Patients requiring revision ACLR in the setting of a MLKI had more overall concurrent surgeries and other ligament reconstructions, but had similar final outcome scores to those who did not require revision surgery. Revision ligament surgery can be associated with increased pain, stiffness, and decrease patient outcomes. Revision surgery is often necessary after multiligament knee reconstructions, but patients requiring ACLR in the setting of a MLKI have good overall outcomes, with patients requiring revision ACLR at a rate of 10%.
Keywords: multiligament knee injury; anterior cruciate ligament; anterior cruciate ligament reconstruction; anterior cruciate ligament revision; knee dislocation